1981
DOI: 10.1093/jat/5.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Organochlorine Pesticides in Specimens from Women Undergoing Spontaneous Abortion, Premature or Full-Term Delivery

Abstract: Organochlorine insecticides (BHC, aldrin, p,p'-DDE, p,p'-DDD, p,p'-DDT) were measured in the blood, placenta and fetus of women experiencing spontaneous abortions, preterm labor or full-term labor using an electron-capture gas chromatographic method. The following trend was found for insecticide concentrations in each of the specimens tested: spontaneous abortions greater than preterm greater than full-term. One conclusion of this work is that the organochlorine insecticides act as antagonists to pregnancy. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(51 citation statements)
references
References 8 publications
2
47
0
Order By: Relevance
“…In mammals, some studies have described relationships between organochlorine pesticides and preterm birth (Longnecker et al 2001;Saxena et al 1981). DDT metabolites are able to impede the binding of some sex steroids (androgen or progesterone) to their receptor through indirect or direct paths, shortening the duration of gestation (Klotz et al 1997;Lyon and Glenister 1980).…”
Section: Data)mentioning
confidence: 99%
“…In mammals, some studies have described relationships between organochlorine pesticides and preterm birth (Longnecker et al 2001;Saxena et al 1981). DDT metabolites are able to impede the binding of some sex steroids (androgen or progesterone) to their receptor through indirect or direct paths, shortening the duration of gestation (Klotz et al 1997;Lyon and Glenister 1980).…”
Section: Data)mentioning
confidence: 99%
“…Recent reports suggested an association between exposure to pesticides and different types of human cancer (Amaral Mendes, 2002;Safi, 2002). The facts that such residues persist in adipose tissue over a period of many decades, are endocrine disrupters, cause immune suppression, and inhibit various enzymes, lead to higher susceptibility to cancer onset (Iscan et al, 2002;Wolff et al, 2000;Safi, 2002;Saxena et al, 1981). Biological monitoring of exposure can be carried out by determination of intact compounds or their metabolites in blood, serum, plasma and urine (Aprea et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…However, in vitro exposure of rat uterine strips isolated from pregnant (Gestation Day 10) rats to cumulative concentrations of lindane at 10-min intervals was found to depress spontaneous contractions at 10 μM lindane and abolish contractions at 30 μM lindane (Criswell and Loch-Caruso, 1999). The inhibitory action of lindane was in contrast to stimulation of uterine contraction frequency that we observed with DDT (Juberg and Loch-Caruso, 1991;Juberg et al, , 1995 and polychlorinated biphenyl isomers (Tsai et al, 1996;Bae et al, 1999a Bae et al, ,b, 2001, which were also elevated in the blood of women who experienced premature delivery or spontaneous abortion (Saxena et al, 1981;Wassermann et al, 1982). We subsequently used lindane as an inhibitor for probing physiologic and pathologic mechanisms of regulation of uterine contraction, and identified a previously unrecognized role for reactive oxygen species (Krieger and Loch-Caruso, 2001) and a previously unidentified myometrial phospholipase A 2 activity (Wang et al, 2001).…”
Section: Introductionmentioning
confidence: 63%
“…In preliminary experiments we observed that uterine strips excised from nearterm (Gestation Day 20) pregnant rats exhibited depressed spontaneous, carbachol-induced, and oxytocin-induced contractions 24 h after a single subcutaneous injection of 4 or 6 mg lindane/kg body weight (unpublished). In women admitted to a hospital in India for obstetrical care who subsequently experienced preterm birth or spontaneous abortion, blood levels of lindane averaged 39.7 ppb (15-79 ppb range, n = 15) and 73.3 ppb (40-136 ppb range, n = 10), respectively (Saxena et al, , 1981. In another study of 17 Israeli women, significantly elevated concentrations of lindane (15 ppb) were detected in serum lipids of women who delivered prematurely compared with women who delivered at term (4.3 ppb) (Wassermann et al, 1982).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation